CLINICAL CHARACTERISTICS, VASCULAR BED INVOLVEMENT AND VASCULAR COMPLICATIONS IN PATIENTS WITH FIBROMUSCULAR DYSPLASIA - POLISH REGISTRY FOR FIBROMUSCULAR DYSPLASIA (ARCADIA-POL). (June 2018) - Warchol-Celinska, E.; Jozwik-Plebanek, K.; Florczak, E.; Prejbisz, A.; Hanus, K.; Januszewicz, M.; Michalowska, I.; Swiatlowski, L.; Talarowska, P.; Janaszek-Sitkowska, H.; Stryczynski, L.; Niemirska, A.; et al.
Abstract : Objective: To assess the clinical characteristics, vascular bed involvement and vascular complications in patients with fibromuscular dysplasia (FMD) enrolled into on-going ARCADIA-POL study. Design and method: Out of 250 patients enrolled into ARCADIA-POL study since January 2015 (instituted on the basis of Polish-French collaboration) we present 183 patients with confirmed FMD in at least one vascular bed. A standardized FMD data form was used for data collection. All patients underwent detailed clinical evaluation including ABPM, biochemical evaluation, biobanking, duplex Doppler of carotid and abdominal arteries and whole body angio-CT. In the following presentation we focused on data on the prevalence of vascular bed involvement and complications. Results: In our analysis we included 183 patients with confirmed FMD (150F[82.0%], 33M[18.0%], mean age: 45.9 ± 15.0 years). 166 patients (90.7%) were hypertensives. The mean age at the diagnosis of hypertension was 35.6 ± 14.7 years and the FMD was diagnosed 6.8 ± 8.6 years later. In the analyzed group FMD was identified in renal arteries in 157 (85.8%) patient as well as in carotid, intracranial and vertebral arteries in 28 (15.3%), 11 (6.0%) and 15 (8.2%) patients, respectively. FMD was also identified in celiac trunk and mesenteric, iliac and splenic arteries in 18 (9.8%), 18 (9.8%), and 4 (2.2%) patients, respectively. Multisite FMD was found in 52 patients (28.4%). Two vascular beds were involved in 19.1%(35 pts), three in 4.9%(9 pts), four in 3.3%(4 pts), five and more in 1.0 %(2 pts). Arterial dissection (s) or aneurysms in various vascular beds were present in 15 (8.2%) and in 58 (31.7%) patients respectively. The most frequently dissections were found in carotid arteries (10 pts, 5.5%). Aneurysms were most often observed in renal and intracranial arteries, in 25 (13.7%) and 21 patients (11.5%). Conclusions: The data of ARCADIA-POL registry showed that renal FMD was the most frequent, but also cerebrovascular FMD was found in relatively large proportion of patients. Our data revealed high incidence of FMD lesions coexisting in different vascular beds as well as relatively frequent occurrence of vascular complications.